Measuring the 2D3/2 Ni- excited state lifetime in DESIREE. (August 2015) - Chartkunchand, K C; Hole, O M; Bäckström, E; Nascimento, R F; Kaminska, M; Davis, V T; Neill, P A; Thomas, R D; Mannervik, S; Thompson, J S; Hanstorp, D; Schmidt, H T; et al.
Synopsis: Experimental studies of the radiative lifetime of the sole excited state in the nickel anion are presented. Beams of Ni - stored in DESIREE at cryogenic temperatures were subject to photodetachment at different photon energies and the resulting neutrals collected. Preliminary analysis of the decay in neutral production yields a radiative lifetime of approximately 15 seconds for the 3 d 9 4 s 2 2 D3/2 excited state.